Prevalência e fatores associados aos comportamentos sedentários em adolescentes - Dias, Paula Jaudy Pedroso (2013)
Background: Technological advances have led individuals to change their lifestyle habits, especially with regard to the adoption of sedentary lifestyle. Knowing the associated factors that lead to the development of sedentary behavior among adolescents is essential for preventing several diseases. Objective: To analyze the factors associated with sedentary behavior. Methods: We studied adolescents aged 10 to 17 years old, both sexes, belonging to a birth cohort between 1994-1999 in the city of Cuiabá, Mato Grosso State, Brazil. We used a questionnaire containing sociodemographic, economic, and lifestyle variables, as well as anthropometric measures. Sedentary behavior was determined as using television and/or computer/video games for a time greater than or equal to 4 hours/day. We evaluated association between sedentary behavior with body mass index in childhood and adolescence, and sociodemographic and behavioral variables using hierarchical logistic regression. Results: The overall prevalence of sedentary behaviors was 58.1%. Among the 1716 adolescents evaluated, 50.7% were male. In multivariate analysis, after adjustment for confounding factors, the variables that remained associated with sedentary behavior were: age (14 years or more) (OR = 3.51, 95% CI 2.19 to 5.60); higher socioeconomic class (OR = 3.83, 95% CI 2.10 to 7.01), higher level of maternal education (OR = 1.81, 95% CI 1.09 to 3.01); live in the country (OR = 0.49, 95% CI: 0.30 to 0.81); insufficient physical activity (OR = 1.25, 95% CI 1.02 to 1.53); experimentation of alcoholic beverages (OR = 1.34, 95 %: 1.08 to 1.66) and overweight in adolescence (OR = 1.33, 95% CI 1.06 to 1.68). Conclusion: The high proportion of adolescents in sedentary activities indicates the need for educational initiatives to reduce multiple risk behavior, particularly among older adolescents from higher-income families and whose mothers have higher schooling.